The shadow value of employer-provided training - Budría, Santiago (2010)
This paper adopts an equivalent income approach to calculate the economic value of training activities for workers. Using econometric regression analysis of individual self-reported job satisfaction (JS) and data from the European Community Household Panel dataset (ECHP), the paper shows that employer-provided training exerts a positive and significant effect on JS. On average, this effect is equivalent to a 17.7% increase in labour earnings. Boes and Winkelmann’s (2009) Generalized Ordered Probit for panel data is used to show that the determinants of JS as well as the equivalent income of training differ across the JS distribution.